Greek Lyric of the Archaic and Classical Periods : From the Past to the Future of the Lyric Subject - Fearn, David (Brill Research Perspectives in Humanities and Social Sciences Ser, 2020)
Intro -- Contents -- Greek Lyric of the Archaic and Classical Periods: From the Past to the Future of the Lyric Subject -- Abstract -- Keywords -- 1 Introduction -- 2 A Preliminary Case Study: Four Readings of Sappho -- 3 Sappho: Wider Ramifications -- 4 Alcaeus, Ibycus, and Anacreon: Sympotic Poetics, Politics, and Erotics -- 4.1 Alcaeus -- 4.2 Ibycus -- 4.3 Anacreon -- 5 Stesichorus: Myth, Narrative, Ornamentation, Interpretability -- 6 Simonides: Tombs and Pictures -- 7 Bacchylides: Narrativity and Imagistic Depth -- 8 Pindar -- 8.1 Pindar In and Out of Context: Contemporary Methodologies -- 8.2 Voices and Attitudes, Lyric Mystifications, or 'Enchanted ethicality' / 'ghost channel:' 'Operationalizing' Pindar -- 9 Timotheus, the New Music, and Beyond: Sound Affects -- References.